2009
DOI: 10.1016/j.neurobiolaging.2007.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Prominent phenotypic variability associated with mutations in Progranulin

Abstract: Mutations in progranulin (PGRN) are associated with frontotemporal dementia with or without parkinsonism. We describe the prominent phenotypic variability within and among eight kindreds evaluated at Mayo Clinic Rochester and/or Mayo Clinic Jacksonville in whom mutations in PGRN were found. All available clinical, genetic, neuroimaging and neuropathologic data was reviewed. Age of onset ranged from 49 to 88 years and disease duration ranged from 1 to 14 years. Clinical diagnoses included frontotemporal dementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
141
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 160 publications
(156 citation statements)
references
References 54 publications
11
141
1
3
Order By: Relevance
“…This is consistent with correlations described in other imaging studies (Caroppo et al, 2014; Ameur et al, 2016; Kelley et al, 2009; Sudre et al, 2017). Using precise anatomical correlation of cadaveric MRI brain images with tissue slices, we were also able to demonstrate that regions with the most severe WMH displayed the most severe cortical pathology on histological analysis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with correlations described in other imaging studies (Caroppo et al, 2014; Ameur et al, 2016; Kelley et al, 2009; Sudre et al, 2017). Using precise anatomical correlation of cadaveric MRI brain images with tissue slices, we were also able to demonstrate that regions with the most severe WMH displayed the most severe cortical pathology on histological analysis.…”
Section: Discussionsupporting
confidence: 92%
“…White matter changes such as gliosis and demyelination have long been observed in histological studies of FTD (Englund & Brun, 1987) and several groups have observed significant WMH on MRI brain scans of GRN mutation carriers with FTD who lack vascular risk factors (Caroppo et al, 2014; Ameur et al, 2016; Kelley et al, 2009; Le Ber et al, 2008; Paternicò et al, 2016; Pietroboni et al, 2011; Sudre et al, 2017). However, studies that have characterized in detail the pathological correlates of WMH in GRN mutation associated FTD have until now been lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our patient also showed a significant improvement of extrapyramidal symptoms after Levodopa treatment (300 mg/day), which is not a common feature in FTDP-17. In fact, the majority of patients carrying a GRN mutation usually show no or modest improvement with Levodopa [4,16], although few cases of responders have been reported [17].…”
Section: Discussionmentioning
confidence: 99%